Low‐Temperature Electron Beam Deposition of Zn‐SnOx for Stable and Flexible Perovskite Solar Cells. Issue 2 (20th August 2019) - Song, Zonglong; Bi, Wenbo; Zhuang, Xinmeng; Wu, Yanjie; Zhang, Boxue; Chen, Xinfu; Chen, Cong; Dai, Qilin; Song, Hongwei
Abstract : Perovskite solar cells (PSCs) attract tremendous interest due to their feasibility, high power conversion efficiency (PCE), light weight, and flexible architecture. However, some challenges are still present for cheap mass fabrication in commercial applications. Herein, efficient Zn‐SnO x electron transport layers (ETLs) are used by the low‐temperature (100 °C) electron beam (E‐beam) method. Doping Zn 2+ in SnO2 improves conductivity, suppresses charge recombination, and optimizes the energy level structure of SnO2, leading to an improved PCE from 18.95% to 20.16%. More importantly, the PCE of the modified device is more than 80% of its initial values for 800 h in ambient air with a relative humidity of ≈40%. The flexible device exhibits a PCE of 15.25% and remains at an initial PCE of 83% after 100 bending cycles. The efficient and flexible PSCs are potentially used as wearable energy power sources. The low‐temperature preparation of ETL and the excellent performance of devices present great commercial potential for future applications. Abstract : Efficient Zn‐SnO x electron transport layers (ETLs) by the low‐temperature (100 °C) electron beam (E‐beam) method are prepared. Doping Zn 2+ in SnO2 improves conductivity, suppresses charge recombination, and optimizes the energy level structure of SnO2, leading to an improved power conversion efficiency from 18.95% to 20.16%. The low‐temperature preparation of ETLs and the excellent performance of devices present great commercial potential for future applications.